(untitled) (Altre Modernità, 2010)
In this paper, I argue that the sociocultural structuring property of whiteness has been utilized to marginalize President Obama and effectively undermine his presidential authority. Whiteness functions in a largely invisible and ostensibly deracialized way to normalize the interests, needs, and values of whites, while at the same time marginalizing and devaluing the voice of people of color. Analyzing the health care debate through this theoretical lens generates insights into how the debate reproduced the system of racial oppression, and how whiteness functions in political discourse.